2005
DOI: 10.1590/s0100-69162005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Análise energética na produção de feno de Cynodon dactylon (L.) Pers

Abstract: O objetivo do trabalho foi caracterizar o consumo de energia na implantação, condução, fenação e armazenamento, assim como a eficiência energética do Cynodon dactylon (L.) Pers, em sistema intensivo de produção de leite, na região de Coronel Pacheco - MG, sendo utilizados dados coletados pela Embrapa Gado de Leite, em média de sete anos. Para o levantamento dos componentes da matriz, foram utilizados coeficientes energéticos preconizados por autores especializados. A energia direta, relativa aos insumos, teve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 9 publications
0
7
0
14
Order By: Relevance
“…Moreover, concerning the use of fuels and lubricants, working with forage crops CAMPOS et al (2005) and CAMPOS et al (2004) observed that fuels and lubricants, respectively, 75.05 and 59.61% of the total energy consumption, assuming greater contribution in the direct energy of the systems studied.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, concerning the use of fuels and lubricants, working with forage crops CAMPOS et al (2005) and CAMPOS et al (2004) observed that fuels and lubricants, respectively, 75.05 and 59.61% of the total energy consumption, assuming greater contribution in the direct energy of the systems studied.…”
Section: Resultsmentioning
confidence: 99%
“…ANGONESE et al (2006) found that pigs for slaughter accounted for 56.8% of the power outputs. SOUZA et al (2009) found out that, from all the energy converted in the system, the energy represented by finishing pigs was equal to 55.58%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations